Achieving small hydropower plant projects sustainability by implementing Logical Framework Approach - Radunovic, Miljan (Industrija, 2020)
Small hydropower plants (SHPPs) play an important role in European energy and infrastructure investment market. They contribute to green energy development and reduction of fossil fuel usage, but also contribute to social and environmental wellbeing of the community. Existing problems arising from SHPP projects throughout Europe, are caused by bad project development, where stakeholders’ interests are misinterpreted and as such incorporated in project plans. Logical Framework Approach with Logical Framework Matrix (LFA/LFM) is a project management tool developed by international financing institutions (IFIs) for the purpose of ensuring reliability and monitoring of allocated funding for complex reconstruction and development projects. Paper assesses key pitfalls of SHPP projects, tracing them back to the planning and design stages, proving that usage of LFA/LFM can prevent them. It advocates for the extensive use of LFA/LFM by investors, arguing that this will ensure lasting SHPP project sustainability in the future.